1978
DOI: 10.1017/s0025315400024437
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals in the Burrowing Bivalve Scrobicularia Plana from the Tamar Estuary in Relation to Environmental Levels

Abstract: Concentrations of ten metals (Ag, Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb, Zn) have been measured in the whole soft parts and digestive gland of the burrowing bivalve Scrobicularia plana (da Costa) over its range of distribution in the Tamar estuary. Four metals (Cu, Fe, Mn, Zn) have been analysed in the individual tissues including the shell. As far as possible, concentrations in the animals have been related to those in the environment. Seasonal variation, level on the shore and size of animal have also been conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0
1

Year Published

1981
1981
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(51 citation statements)
references
References 21 publications
4
46
0
1
Order By: Relevance
“…In the present study, the increase observed in the average lead concentrations in October and December coincided with an increase in the weight: size ratio. A similar observation was recorded by BRYAN & UYSAL (1978) who found an increase in lead concentration with increasing dry weight of whole soft body parts of the bivalve, Scrobicularia plana, from the Tamar Estuary in England. PHILLIPS (1978) reported concentrations of lead in mussels to be highest in mussels taken from low-salinity waters on the Scandinavian coasts.…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, the increase observed in the average lead concentrations in October and December coincided with an increase in the weight: size ratio. A similar observation was recorded by BRYAN & UYSAL (1978) who found an increase in lead concentration with increasing dry weight of whole soft body parts of the bivalve, Scrobicularia plana, from the Tamar Estuary in England. PHILLIPS (1978) reported concentrations of lead in mussels to be highest in mussels taken from low-salinity waters on the Scandinavian coasts.…”
Section: Discussionsupporting
confidence: 85%
“…For example, metals may vary in both concentration and total body load in bivalves with age or size (Boyden, 1974(Boyden, , 1977Bryan and Uysal, 1978). Season may also be a significant perturbant of element levels (Bryan, 1973;Frazier, 1975Frazier, , 1976Phillips, 1976a).…”
Section: Introductionmentioning
confidence: 99%
“…1978). Such correlations are most common in metalenriched environments (Boyden, 197'7;Bryan and Uysal, 1978;Strong and Luoma, 1 981) and appear to reflect lifelong, net metal accumulation (Cross and others, 1973). Recent studies point to mechanisms that might explain how lifelong metal accumulation could occur in enriclJ.ed environments coincident with metal fluxes that should eventually lead to a steady-state concentration.…”
Section: Characteristics Of the Biological Uptake Of Metalsmentioning
confidence: 99%
“…Only animals exposed to methylmercury in food showed distributions similar to those observed in fish from nature, leading to the conclusion that food was the source of the metal. Bryan and Uysal (1978) concluded from tissue distributions that Cd, Co, Pb, and Zn, but possibly not Ag and Cu, in the burrowing clam Scrobicularia plana originated largely from food.…”
mentioning
confidence: 99%